THEORY AND PRACTICE OF FERTILIZER AND FOLIAR APPLICATIONS IN PLANTATIONS OF APPLE AND PEAR CROPS - Слюсаренко, В. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The studies results on the application of fertilizers in pear plantations in Ukraine and abroad are considered. In the system of caring for fruit plantations; including for pomegranate crops; rational; effective under certain conditions of application of fertilizers are of great importance. To meet the needs of the economic complex and the population of the country in the horticulture production; it is necessary to significantly increase the productivity of fruit plantations. Data on the development of an optimal system for fertilizing intensive plantations of pears on a vegetative rootstock under Ukrainian conditions has been relatively few. Therefore; the issue of studying the productivity of a pear garden for optimizing mineral nutrition when applying a rational fertilizer system in the conditions of the Southern Steppe of the North-Western Black Sea Coast of Ukraine is relevant. The article offers an overview of domestic and foreign literary sources about the theory and practice of fertilization and foliar application of fruit crops; including trees of pome fruits